2021
DOI: 10.3390/toxins13070474
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antifibrotic Effects of Fraxetin on Renal Interstitial Fibrosis via the ERK Signaling Pathway

Abstract: Fraxetin, a natural derivative of coumarin, is known to have anti-inflammatory, anti-oxidant, and hepatoprotective effects in multiple diseases and in liver fibrosis. Whether fraxetin exerts similar effects against renal fibrosis is unknown. In a Unilateral Ureteral Obstruction (UUO) mouse model of renal fibrosis, fraxetin decreased UUO-induced renal dysfunction with a marked reduction in renal interstitial collagen fibers as detected by Masson’s Trichrome staining. Fraxetin treatment also inhibited the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…An interesting finding was that coumarin derivatives, including fraxetin, may enhance the production of IL-10 and IFN-α which are well documented to abrogate the inflammasome-driven augmentation of the in-flammatory process [39,40]. Moreover, TGF-β1 which is proven to initiate activation of the NLRP3 inflammasome and induce epithelial-to-mesenchymal transition with subsequent fibrosis is effectively inhibited by fraxetin administration [41].…”
Section: Discussionmentioning
confidence: 99%
“…An interesting finding was that coumarin derivatives, including fraxetin, may enhance the production of IL-10 and IFN-α which are well documented to abrogate the inflammasome-driven augmentation of the in-flammatory process [39,40]. Moreover, TGF-β1 which is proven to initiate activation of the NLRP3 inflammasome and induce epithelial-to-mesenchymal transition with subsequent fibrosis is effectively inhibited by fraxetin administration [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, fraxetin was reported to be effective in protecting the liver, kidneys, and heart. [ 6,30–33 ] These reports suggest that fraxetin may serve as a promising anticancer drug. Our data revealed that fraxetin inhibited viability and promoted apoptosis of bladder cancer cells in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Fraxetin (7,8‐dihydroxy‐6‐methoxy coumarin) is a natural compound extracted from the Chinese herb Cortex Fraxini . [ 5,6 ] Fraxetin has been widely used in Chinese traditional medicine, and it serves as the essential ingredient of many dietary and herbal supplements. [ 7–9 ] Fraxetin is readily available and relatively cheap and is known to have few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, HDHW components were identified by UHPLC-Q-Orbitrap-MS/MS and 14 components were identified. Among these 14 ingredients, the anti-renal fibrosis effects of Linoleic acid (Zhan et al, 2015;Zhou et al, 2017), Oleanolic acid (Zhao and Luan, 2020), Nicotinamide (Kumakura et al, 2021), Rutin (Han et al, 2015;Wang et al, 2016), Gallic acid (Yousuf and Vellaichamy, 2015), Ferulic acid (Mir et al, 2018;Qi et al, 2020), Fraxetin (natural derivatives of coumarin) (Hsieh et al, 2021), and Theophylline (adenosine antagonist) (Tang et al, 2015) have been demonstrated. They exert antifibrotic effects mainly through autophagy regulation, apoptosis regulation, antioxidant, and anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%